Leveraging AI in Healthcare: Innovations in Fraud Detection and Novel Approaches to Cancer Medicine - Muhammad Umer Qayyum; Muhammad Fahad; Muhammad Ibrar; Ali Husnain (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
Artificial intelligence (AI) has revolutionized fraud detection and cancer treatment by providing cutting-edge technologies that improve patient outcomes, efficiency, and accuracy. Healthcare systems can protect themselves from financial losses and ensure the seamless processing of valid claims by implementing individualized prevention methods and real-time analysis through the use of AI-driven fraud detection systems, which are getting more and more complex. AI is pushing the limits of early detection, precision medicine, and drug development in the field of cancer medicine, enabling more individualized and efficient treatments. But the use of AI in these domains also presents significant moral and legal issues, such as worries about prejudice, responsibility, openness, and patient privacy. To address these issues and guarantee that AI is applied responsibly and that its advantages are shared fairly, strong legal frameworks, international cooperation, and well-defined ethical standards must be established. It is anticipated that as AI develops, its application in healthcare will grow, spurring additional innovation and requiring a delicate balancing act between ethical concerns and technical advancements. In the end, AI has the potential to improve healthcare delivery in ways that are more effective, efficient, and egalitarian, but this will rely on how these formidable technologies are developed and used responsibly.